Synthesis of 4-difluoromethylquinolines by NHC-catalyzed umpolung of imines - Patra, Atanu (Organic Letters, 2018)
The N-heterocyclic carbene (NHC)-catalyzed umpolung of aldimines for the synthesis of 4-difluoromethylquinoline derivatives is reported. In the presence of NHCs, the intramolecular cyclization of aldimines bearing a moderately electron-poor double bond due to the presence of the −CF3 group likely proceeds via the intermediacy of the aza-Breslow intermediate. The key to the success of this aza-Stetter type transformation is the NHC generated from the bicyclic triazolium salt using DBU as the base.